THE NEED FOR JOINT PLANNING OF ORTHOPEDIC DENTAL CARE IN COMPLEX TREATMENT OF PATIENTS WITH DEFECTS OF MAXILLOFACIAL LOCALIZATION - L.I. Voloshyna (Український стоматологічний альманах, 2016)
The study of the problem and satisfaction of the population with medical and dental care is extremely important. Definition of the need for specialized dental treatment of patients with defects of maxillofacial localization has become of special relevance and gained a greater social significance in the recent years.